2015
DOI: 10.1098/rsta.2014.0414
|View full text |Cite
|
Sign up to set email alerts
|

The impact of parametrized convection on cloud feedback

Abstract: We investigate the sensitivity of cloud feedbacks to the use of convective parametrizations by repeating the CMIP5/CFMIP-2 AMIP/AMIP + 4K uniform sea surface temperature perturbation experiments with 10 climate models which have had their convective parametrizations turned off. Previous studies have suggested that differences between parametrized convection schemes are a leading source of inter-model spread in cloud feedbacks. We find however that ‘ConvOff’ models with convection switched off have a similar ov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
93
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(99 citation statements)
references
References 93 publications
4
93
0
Order By: Relevance
“…Previous studies have shown lower tropospheric stability (LTS) to be a useful diagnostic tool that connects low-cloud changes to the characteristics of the large-scale environment, especially within traditionally defined stratocumulus regions (Klein & Hartmann, 1993;Medeiros et al, 2008;Webb et al, 2015;Wood & Bretherton, 2006). We analyze the EIS, which can be thought of as a correction to the LTS based on the moist adiabatic profile.…”
Section: Methodology Of Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown lower tropospheric stability (LTS) to be a useful diagnostic tool that connects low-cloud changes to the characteristics of the large-scale environment, especially within traditionally defined stratocumulus regions (Klein & Hartmann, 1993;Medeiros et al, 2008;Webb et al, 2015;Wood & Bretherton, 2006). We analyze the EIS, which can be thought of as a correction to the LTS based on the moist adiabatic profile.…”
Section: Methodology Of Analysismentioning
confidence: 99%
“…They, as did most previous studies (e.g., Klein & Hartmann, 1993;Wood & Bretherton, 2006), focused on five oceanic regions which are important for stratocumulus decks of radiatively active lowlevel clouds. Only recently have the fields of stability, low-level clouds, and low-level temperature begun to be investigated over larger swaths of the globe (Grise & Medeiros, 2016;Rose & Rayborn, 2016;Webb et al, 2015;Zhou et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Last but not least we investigate the impact of parameterized convection on ECS by performing a simulation in which we completely switched off convection (simulation NOCONV) as in Webb et al (2015). This is normally performed only in simulations run at horizontal resolutions of less than 10 km, at which the vertical motions associated with deep convection start to be resolved.…”
Section: Model Set-up and Experimentsmentioning
confidence: 99%
“…There are discussions if cirrus clouds are mainly formed by homogeneous nucleation as we assume in our reference simulation or are formed heterogeneously (Cziczo et al, 2013;Spichtinger and Krämer, 2012;Kärcher, 2017). We investigate the impact of homogeneous vs. heterogeneous freezing in cirrus and ECS by performing a simulation in which we completely switched off convection (simulation NOCONV) as was done in Webb et al (2015). This is normally done only in simulations run at horizontal resolutions of less than 10 km, where the vertical motions associated with deep convection start to be resolved.…”
Section: Model Set-up and Experimentsmentioning
confidence: 99%